Optimization of chitosan level to alleviate the drastic effects of heat stress in cucumber (Cucumis sativus L.) - Ali, Mujahid; Ayyub, Chaudhary Muhammad; Hussain, Zahoor; Hussain, Rashid; Rashid, Shahla (Journal of Pure and Applied Agriculture, 2023)
Heat stress is a major concern during cucumber production. To explore its production potential, chitosan could play a vital role in alleviation of heat stress. This study was planned to evaluate the potential of chitosan in cucumber growth where it is more effective under high temperature with two factorial under Completely Randomized Design (CRD). Four genotypes were previously screened out; two were tolerant (L3466, Desicucumber) and two were sensitive (Suyo Long and Poinsett). These genotypes were grown in the growth room having a normal temperature (28°C/22°C day/night). One day before heat treatment (40 ºC/32 ºC day/night), chitosan foliar spray with different concentrations (0, 50, 100, 150,